Organogels based on amino acid derivatives and their optimization for drug release using response surface methodology. Issue 1 (1st January 2020) - Hu, Beibei; Yan, Haipeng; Sun, Yanping; Chen, Xi; Sun, Yujuan; Li, Sanming; Jing, Yongshuai; Li, Heran
Abstract: Organogels are excellent drug carrier for controlled release. Organogels based on amino acid derivatives has been widely used in the area of drug delivery. In this study, a series of the organogel system based on amino acid derivatives gelators was designed and prepared to investigate the structure-property correlation in organogels. To investigate the factors that influence the property of drug release, we varied the formulation in the organogels: gelator structure, gelator concentration, volume of antigelation solvent, and drug loading. Through the Box–Behnken tests, the optimum organogel formulation in vitro was obtained. The self-healing properties of the organogel have been utilised for injection of a model lipophilic risperidone in situ, and sustained release of the drug has been studied over about one week in vivo . In conclusion, the gelation ability of gelators could be adjusted by the gelator structure. Gel property is related with the whole composition of the formulation. As drug carrier, the drug release property of organogels is affected by multiple factors. Our investigation of the gel release property will play a theoretical guiding role in the application in the in situ drug delivery system.